(untitled) (NAU Journal of Library and Information Science, 2026)
The study was conducted to examine social media platform for information service delivery by Nigerian federal university libraries. Four (4) research objectives guided the conduct of the study. One (1) null hypothesis was tested at 0.05 level of significance to test the relationship between variables of the study. Quantitative research methodology using survey research design was used. The population of the study comprised 243 system staff from 33 federal university libraries in Nigeria that used social media. Total enumeration was used to include all the system staff. Questionnaire was the instrument was used for data collection. The data collected was analyzed using descriptive statistics and inferential statistics. The findings revealed that Facebook, LinkedIn, Google+, Blog and Twitter (also X) were used in the libraries studied and more frequently than other types of social media. They were used to deliver current awareness service, dissemination of library event and reference service. Challenges associated with the use of social media by the libraries include low presence of social media on websites, inadequate infrastructure to access IT facilities among others. Hypothesis test showed that the alternative hypothesis was accepted and the null hypothesis was rejected which signifies relationship between the variables. It was recommended to the system staff to explore other types of social media such as RSS feed, podcast and other emerging social media that may have features to fit into information services of the libraries. This would help the library diversify the scope of its service provision to include as Selective Dissemination of Information (SDI), assistance in the use library tools (OPAC) among others.